Injustice Towards Human Rights in America After Civil Right Movement in Play The Pillowman By Martin Mcdonagh (2003) - Ratih Melati Sukma; Muhd. Al-Hafizh (English Language and Literature, 2022)
This thesis is an analysis of a play written by Martin Mcdonagh entitled The Pillowman (2003). This analysis look at the injustice after civil right movement is not only in real life, but in literature there is a problem the injustice that attacks the lower class because their profession considered lowly than the upper class. This analysis employs Marxist literary theory to explain the phenomena in the play. In this analysis, the protagonist’s injustice towards human rights can been seen through two ways: how he faces and shows several forms of the injustice towards human rights in America after civil right movement that still occurred. This analysis also depends a lot on the narrator to determine which parts of the play are used as the data. The result of the study shows that Katurian experienced injustice to get his righs and injustice in law.